(untitled) (Chittagong University Journal of Biological Sciences, 2013)
Histopathological studies of gill, liver and intestine of the experimental fishes Heteropneustes fossilis (Bloch) were made after 24 hours exposure to 50% ethyl alcohol extracts of Madhuca indica (G. F. Gmel) plant parts. The principal changes in the gills included distorted and disintegrated gill arches, shrunken and oedamatous distensions in the primary lamellae, swollen, shortened and coalesced secondary lamellae, vacuolated and disrupted epithelial and pilaster cells and disorganized gill filaments. The changes in the liver included compactly or loosely arranged hepatic cells, dialated and swollen central vein, blood coagulated portal vein, reduced or swollen hepatic artery and dispersed sinusoids. In the intestine disintegrated serosa, swollen and partially ruptured muscularis, vacuolated submucosa, damaged mucosa, disintegrated and reduced lamina propria and distended and coalesced villi were observed. On the basis of affectivity the most affected organ was the gill followed by liver and intestine. Affectivity of the plant parts on the three organs was in the order seed > bark > leaf for gill, intestine and was seed > leaf > bark for liver. DOI: http://dx.doi.org/10.3329/cujbs.v4i1.13395 The Chittagong Univ. J. B. Sci.,Vol. 4(1&2):119-130, 2009